Membangun Kesadaran dan Partisipasi Masyarakat Sukawati Dalam Pemilahan Sampah untuk Lingkungan Berkelanjutan - Decky Cipta Indrashwara; Dewa Ayu Trisna Adhiswari Wedagama; I Gede Fery Surya Tapa; I Nyoman Indra Kumara; Kenny Christovorus Manek (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to increase awareness and participation of the Sukawati, Gianyar community in waste sorting efforts as an initial step towards a sustainable environment. The problem of waste management in this area is still a major challenge, especially related to the lack of knowledge and awareness of the community regarding the importance of waste sorting. This activity includes socialization and education through counseling, group discussions, and direct practice at the Pasar Seni Sukawati, Gianyar. Socialization and group discussion focuses on explaining the types of waste, the benefits of sorting, and the negative impacts of improper waste management. Direct practice was carried out by educating traders at the Pasar Seni Sukawati in sorting organic, inorganic, and residual waste and utilizing recyclable waste. The results of this activity show an increase in public knowledge and awareness of the importance of waste sorting. In addition, active community participation in this activity indicates a commitment to implementing waste-sorting habits in everyday life. This community service activity contributes directly to the Sukawati, Gianyar community by increasing awareness and participation in waste sorting, to create a cleaner and healthier environment.